Determination of Corporate Social Responsibility (CSR) and Environmental Performance on Profitability in Manufacturing Companies - Anastasia Anggarkusuma Arofah (Cita konsultindo, 2024)
The purpose of this study is to empirically examine the effect of Corporate Social Responsibility (CSR) and Environmental Performance on the Profitability Level which is proxied by the Return On Equity (ROE) ratio in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019 – 2021. Using on 20 manufacturing companies, Corporate Social Responsibility and Environmental Performance being factor in affecting probability level. The type of data used in this research is quantitative data and the data source is secondary data. The data of research was analyse using SPSS software version 26 multiple linear regression analysis. The result of research shows that Corporate Social Responsibility (CSR) has a significant negative effect on the company's profitability level and Environmental Performance has a significant positive effect on the company's profitability level. Moreover, the significance of Corporate Social Responsibility (CSR) and Environmental Performance has important implications for the development of policies that aim to improve profitability among manufacturing companies.